Cytoskeletal organization through multivalent interactions - Braun, Marcus; Diez, Stefan; Lansky, Zdenek (Journal of cell science, 2020)
The cytoskeleton consists of polymeric protein filaments with periodic lattices displaying identical binding sites, which establish a multivalent platform for the binding of a plethora of filament-associated ligand proteins. Multivalent ligand proteins can tether themselves to the filaments through one of their binding sites, resulting in an enhanced reaction kinetics for the remaining binding sites. In this Opinion, we discuss a number of cytoskeletal phenomena underpinned by such multivalent interactions, namely (1) generation of entropic forces by filament crosslinkers, (2) processivity of molecular motors, (3) spatial sorting of proteins, and (4) concentration-dependent unbinding of filament-associated proteins. These examples highlight that cytoskeletal filaments constitute the basis for the formation of microenvironments, which cytoskeletal ligand proteins can associate with and, once engaged, can act within at altered reaction kinetics. We thus argue that multivalency is one of the properties crucial for the functionality of the cytoskeleton.
Keywords: Molecular Motor Proteins; Cytoskeleton; pohyb buněk; Microtubules; proteiny; Cell Movement; mikrotubuly; molekulární motory; cytoskelet; Proteins